2005
DOI: 10.1158/1078-0432.ccr-04-2275
|View full text |Cite
|
Sign up to set email alerts
|

N 1,N12-Diacetylspermine as a Sensitive and Specific Novel Marker for Early- and Late-Stage Colorectal and Breast Cancers

Abstract: -diacetylspermine (DiAcSpm) in the urine of colorectal and breast cancer patients was examined to establish its usefulness as a novel diagnostic tool for detecting these cancers at clinically early stages. Experimental Design: Urine samples from 248 colon cancer patients and 83 breast cancer patients as well as 51patients with benign gastrointestinal diseases treated inTokyo Metropolitan Komagome Hospital during the period of August1999 toJanuary 2004 were collected. DiAcSpm was analyzed by ELISA and its sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 13 publications
4
63
0
Order By: Relevance
“…6,11Y13 In breast cancer, even earlystage disease seems to be associated with elevated levels of DiAcSpm in the urine. 13 In colon cancer, urinary DiAcSpm may be a better tumor marker than carcinoembryonic antigen or cancer antigen 19-9. 13,14 Besides being predictive markers, there is a possibility that DiAcSpm and DiAcSpd could be used also as prognostic markers, at least in testicular or prostatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6,11Y13 In breast cancer, even earlystage disease seems to be associated with elevated levels of DiAcSpm in the urine. 13 In colon cancer, urinary DiAcSpm may be a better tumor marker than carcinoembryonic antigen or cancer antigen 19-9. 13,14 Besides being predictive markers, there is a possibility that DiAcSpm and DiAcSpd could be used also as prognostic markers, at least in testicular or prostatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hiramatsu et al [90] studied N 1 N 12 -diacetylspermine as a potential urinary biomarker in breast cancer. This protein deriving from the polyamine metabolism in association with cell proliferation was significantly up-regulated in 80.3% of urines examined in 51 women with late-stage and metastasized breast cancer as compared to a healthy control cohort ( n = 51).…”
Section: How Women With Breast Cancer Could Be Monitored (Non-invasivmentioning
confidence: 99%
“…Interestingly, the same group of patients was simultaneously tested for their serum CA 15–3 and CEA levels. Even though these proteins have been suggested as potential monitoring biomarkers in the past, they accounted for a lower sensitivity of 60.8 and 58.8%, respectively [89, 90]. Beretov et al [91] chose a liquid chromatography with tandem-mass spectrometry approach to discover novel urinary protein biomarker candidates for breast cancer metastasis.…”
Section: How Women With Breast Cancer Could Be Monitored (Non-invasivmentioning
confidence: 99%
“…An untargeted global metabolomics analysis revealed that an elevated N(1), N (12)-diacetylspermine pool, a polyamine relevant to oncogenesis, was in part due to contribution(s) from the bacterial biofilms. While excess levels of various polyamines have been recognized in association with colon cancer, including one study in which N(1), N (12)-diacetylspermine was detected in the urine of CRC patients, 5 this is the first direct link of this polyamine metabolite to the microbiome and, specifically, biofilm formation. A decreasing gradient from the proximal to distal colon in both healthy and disease states has been reported for polyamine levels and ornithine decarboxylase (ODC) prior to our study.…”
Section: Introductionmentioning
confidence: 99%